2011
DOI: 10.1017/s1479262111000268
|View full text |Cite
|
Sign up to set email alerts
|

Identifying QTLs for cold-induced resistance to Microdochium nivale in winter triticale

Abstract: Snow mould caused by Microdochium nivale (Fr.) Samuels & Hallett is the most widespread seedling disease in winter cereals. Due to the complexity of the resistance mechanisms, a poorly understood genetic background and strong interaction with winter weather conditions, it is difficult to assess the resistance of triticale cultivars via conventional inoculation methods. Genetic resistance is the most economical and environmental friendly way to control M. nivale infection; therefore, the objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…), a man-made hybrid crop [2] with great yielding potential particularly in severe culture conditions. Variable levels of M. nivale infection in triticale were reported from field experiments and from testing at control 1 3 conditions [3][4][5], but no fully resistant genotype was found. The fungicides used so far against M. nivale are very harmful to the environment and not sufficiently effective [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), a man-made hybrid crop [2] with great yielding potential particularly in severe culture conditions. Variable levels of M. nivale infection in triticale were reported from field experiments and from testing at control 1 3 conditions [3][4][5], but no fully resistant genotype was found. The fungicides used so far against M. nivale are very harmful to the environment and not sufficiently effective [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The fungicides used so far against M. nivale are very harmful to the environment and not sufficiently effective [6][7][8]. Only cold-hardening is regularly reported to induce increased resistance against pink snow mould [4,5,[9][10][11][12][13][14], but its effect is genotype-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…'Saka 3006' and 'Modus' was used for identification of QTLs associated with albino plant production by anther culture method. The same mapping population together with produced for it well-saturated genetic linkage map (Tyrka et al 2011) was successfully used in several previous studies Szechynska-Hebda et al 2011;_ Zur et al 2012). Among others, the QTLs associated with androgenic structure formation and green plant regeneration has been identified .…”
mentioning
confidence: 99%
“…In our previous studies we have shown that a cold-hardening treatment induces the resistance of winter triticale to the infection of m. nivale (Gołębiowska, Wędzony 2009;Gołębiowska et al 2011;Dubas et al 2011;Szechyńska-Hebda et al 2011;Żur et al 2013). Without hardening, seedlings of studied triticale cultivars: Hewo and Magnat were completely damaged by m. nivale mycelium.…”
Section: Abbreviationsmentioning
confidence: 93%